Using choice experiments to improve the design of agri-environmental schemes. (13th June 2019) - Latacz-Lohmann, Uwe; Breustedt, Gunnar
Abstract: This study applies a two-stage analysis of discrete–continuous supply of environmental services, based on an extended discrete choice experiment (DCE) with 68 farmers in Northern Germany. The estimation strategy combined a multinomial Heckman model and an OLS regression. We extend the literature by feeding the estimation results into a contract optimisation model for a stylised conservation scheme. The optimised contract differed significantly from the standard contract, which offered farmers a payment equal to the average cost of service provision. The standard contract yielded only 64 per cent of the environmental service of the optimised contract for the same budget outlay.